Quantitative analysis of financial market infrastructures: further perspectives on financial stability - Tatu Laine (Bank of Finland, 2015)
This simulator seminar book includes twelve chapters dealing with various aspects of quantitative analysis of financial market infrastructures. The topics include, among others, systemic risks, participant behavior, and new monitoring methods of various payment systems. The methodologies vary from payment system simulations to other types of quantitative analysis based e.g. on artificial neural networks as well as GARCH models. These studies have been presented in the Bank of Finland's simulator seminars during 2012–2014.
URN:NBN:fi:bof-201512221501
Keywords: C15; C81; C92; D53; D70; E42; E58; G01; G21; 330; simulation; payment system; settlement system; liquidity; systemic risk; indicators; free riding; behavioral modeling; RTGS; Finanzmarkt; Simulation; Zahlungsverkehr; Projektbewertung; Clearing; Liquidität; Systemrisiko; Anlageverhalten; Trittbrettfahrerverhalten; Verhaltensökonomik; Neuronale Netze; ARCH-Modell